Meningkatkan Mutu Pendidikan Karakter Melalui Film â€œSokola Rimbaâ€ - Payuyasa, I Nyoman; Primayana, Kadek Hengki (Jurnal Penjaminan Mutu, 2020)
Education serves to improve intellectual intelligence and human character. Character education must go through a learning process. The education process in the Covid-19 pandemic situation was forced to be carried out online. This situation will hamper the student's character learning process. Aside from being an entertainment, film becomes an educational media for the community. The film "Sokola Rimba" is a film that has educational and humanitarian values. Therefore it is important to conduct research on the character value of the film "Sokola Rimba". To improve the quality of character education for students who learn from home. This research will analyze the character values in the film "Sokola Rimba", to improve the quality of character education. This research is a descriptive qualitative research with an observation method. The results of this study are in the film "Sokola Rimba" there are ten character values. The character values are social care, hard work, responsibility, tolerance, religious, care for the environment, love for peace, curiosity, creative, and friendly. The values in the "Sokola Rimba" film can be used as a medium to improve the quality of character education when students learn from home.